Digital Readiness of School Counselors for Hybrid Counseling: A Scoping Review and a Multilevel Competency Framework - Eko Susanto; Yuni Novitasari (Universitas Muhammadiyah Metro, 2026)
Digital transformation has altered how school counseling is organized, delivered, documented, and extended beyond the physical school setting. Yet the literature uses heterogeneous terms including online counseling, virtual counseling, tele-counseling, digital counseling, technology integration, web-based guidance, and artificial intelligence making it difficult to determine what “readiness” for hybrid school counseling should encompass. This scoping review maps the recent Scopus-indexed literature relevant to school counselors’ digital readiness and technology-mediated practice. A supplied Scopus export containing 100 records was screened in two stages. The temporal window was restricted to the most recent ten calendar years (2017–2026), and only records classified by Scopus as Document Type “Article” were eligible. This produced 48 records for title-and-abstract relevance screening. Eighteen sources met the Population–Concept–Context criteria and were included. The evidence base was geographically concentrated in the United States and Indonesia and methodologically diverse, comprising quantitative, qualitative, mixed-methods, research-and-development/system-development, and conceptual sources. Five overlapping themes were identified: practitioner digital readiness and adaptive competence; digitally mediated and hybrid service delivery; digital assessment, data, and program infrastructure; organizational and ethical conditions; and artificial intelligence and future-ready counseling. Digital self-efficacy, role clarity, institutional support, privacy, access, relationship quality, and human oversight repeatedly emerged as readiness conditions. A central gap is that the literature frequently examines online, virtual, or digital components but rarely operationalizes hybrid school counseling as a distinct, intentionally integrated service model. The review therefore proposes a multilevel readiness framework in which individual, practice, organizational, and ethical-relational readiness jointly shape hybrid counseling capability. Future research should validate multidimensional readiness measures, compare hybrid and single-modality counseling, and test implementation models across diverse school systems.